Penegakan Hukum Terhadap Pemberantasan Terorisme Pada Obyek Vital (Studi Pada Kepolisian Daerah Sumatera Utara) - Hanafi Harahap; Isnaini Isnaini; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to show that the legal rules regarding the eradication of terrorism are regulated in Law No. 5 of 2018 concerning Amendments to Law No. 15 of 2003 concerning the Stipulation of Perpu No. 1 of 2002 concerning the Eradication of Criminal Acts of Terrorism. Law enforcement against the eradication of terrorism in Vital Objects in the North Sumatra Regional Police refers to the theory of law enforcement according to Soerjono Soekanto that law enforcement has 3 elements, namely: first, legal certainty (rechtssicherheit), second; Benefits (zweckmassigkeit), and third, Justice (gerechtigkeit). The research method used is a normative juridical research with analytical descriptive research characteristics. This study uses materials obtained from the results of library research, from library research secondary data is collected which includes primary legal materials, secondary legal materials and tertiary legal materials. Data analysis in this study is qualitative. The results showed that the opportunity for the police to take preventive action, namely to prohibit and process the law of all public actions that could be categorized as leading to radicalism or terrorism refers to law enforcement theory.